Improving Women's Economic Empowerment: The Roles of UNCTAD - Feby Diah Miranti; Deasy Silvya Sari (Pusat Studi Gender Universitas Jember, 2023)
The connection between gender and economic issues is now inseparable. When an economic policy is implemented it will have an impact on women's lives. Therefore, an IGO role is urgently needed in accelerating awareness and promotion related to the economy and gender equality. This article will explain what roles UNCTAD has played to empower women's economy in developing countries from many regions. This research used qualitative method and data collection through literatures, official documents, news, and websites. The roles performed are based on three levels, namely at the level of the international system, state, and individual.